Review of Online Discussion Board to Improve Academic Achievement in Pandemic Time Learning - Sudarmo, Sudarmo (Tapis: Jurnal Penelitian Ilmiah, 2020)
This article analyzed online board discussions' effectiveness as an alternative learning method in response to health protocol policies and compulsory education during Indonesia's pandemic emergency. Since COVID-19 hit in the world, WHO and UNESCO have obliged all countries has been applying technology-assisted distance learning. To get the learning application's effectiveness using the online discussion board method. The researcher analyzed fifteen findings of learning experts during the pandemic, which were published in international journals. The researcher analyzed qualitatively through coding, in-depth interpretation and concluding and ensures that the findings were valid and reliable. The results showed that the online discussion board has become an alternative method during learning during the COVID-19 period, such as podcast applications, ZOOM, Google Classroom. Therefore, the researcher recommends that applying this online discussion as most method was recommended to improve learning and maintain safety during a pandemic. Keywords: Online Discussion Board, Improving Academic Achievement, Learning in Pandemic